The Readiness of Indonesian Space Defence - Jeanne Francoise; Santalia Leuwayan (President University, 2023)
AbstractThis academic paper is aimed to analyze how far is ASEAN member countries, as well as Indonesia to implement the ideas of space defence programmes. For analyzing the factor of current geopolitics, this paper is using the theory of neorealism, for analyzing the readiness of space defence, this paper is using Republic of Indonesia’s national defense strategy, which includes inward looking and outward looking, then to analyze the implementation of the programmes of space defence, this paper is using dual use of civil defense. This paper will be the first eye opener about the importance and urgency of space defence as part of people’s nationalism, identity, modernism, and economy.Keywords: space defence, neorealism, ASEAN, Indonesia, nationalism,geopolitics